LEGAL ANALYSIS OF THE APPLICATION OF ALTERNATIVE CHARGES IN SEXUAL VIOLENCE CASES FOLLOWING THE ENACTMENT OF THE TPKS LAW (Study of Decision Number 99/Pid.Sus/2024/PN Lubuk Pakam) - Ferry Wira Padang; Andi Maysarah; Dian Hardian Silalahi (NOMOI Law Review, 2026)
The enactment of Law Number 12 of 2022 (UU TPKS) creates a legal intersection with the Criminal Code (KUHP) in prosecuting sexual violence, necessitating strategic alternative indictments. This research analyzes the juridical application of alternative charges in Decision Number 99/Pid.Sus/2024/PN Lubuk Pakam to determine the validity of applying the KUHP after the enforcement of UU TPKS. Utilizing a normative juridical method with a case study approach, this study evaluates the judge's considerations regarding the lex specialis derogat legi generali principle. The discussion reveals that while the Public Prosecutor presented alternative charges combining Article 285 KUHP and Article 6 of UU TPKS, the Panel of Judges prioritized the KUHP indictment. This decision was grounded in the specific facts the use of a sharp weapon and physical force which aligned more precisely with the element of violence in the KUHP rather than the abuse of authority emphasized in the UU TPKS. The analysis confirms that enforcing general law is legally justified when factual violence outweighs relational exploitation. The conclusion asserts that the 12-year imprisonment satisfies the sense of justice. It is suggested that law enforcers maintain flexibility in selecting articles that best represent the modus operandi to ensure effective prosecution.